Diagnosis of polycystic ovaries syndrome: establishment of reference values of nine hormones on Maglumi X- 8 - Aamir Ijaz; Shakila Khadim; Insharah Ali Sahi; Ayesha Akbar; Sara Saeed; Farhan Ahmed; Khalid Muhammad; Yasir Waheed (Middle East Fertility Society Journal)
Abstract Background Polycystic ovary syndrome (PCOS) is one of the most common causes of infertility. Availability of some hormones like free testosterone (fT), dehydroepiandrosterone sulfate (DHEAS), anti-Müllerian hormone (AMH), and androstenedione (A4) assay on a user-friendly immunoassay system will be a milestone in the diagnosis of PCOS. Aim of the study was to establish reference values of fT, total testosterone (TT), luteinizing hormones (LH), follicle stimulating hormones (FSH), prolactin (Prl), estradiol (E2), DHEAS, AMH, and A4. Results Serum specimens of 135 disease-free adult females were collected from Mohi Uddin Teaching Hospital, Mirpur, AJ&K, Pakistan (MOTH) which is the affiliated hospital of Mohi Uddin Islamic Medical College, Mirpur, AJK, Pakistan (MIMC) and after obtaining written informed consent. Blood specimens were analyzed in the Pathology Laboratory of MOTH using state-of-the-art fully automatic chemiluminescence analyzer Maglumi X8 (Snibe, China) for all nine parameters. Reference values of fertility hormones were AMH: 0.84–10.2 ng/mL (14.3–49.0 pmol/L); A4: 10.5–50.9 ng/dL (3.7–17.8 mmol/L); DHEAS: 81–426 µg/dL (0.8–10.2 µmol/L); E2: 18.9–147 pg/mL (70–542 pmol/L); fT: 0.5–2.57 pg/mL (1.7–8.9 pmol/L); FSH (follicular phase): 2.36–13.1 mIU/mL; LH (follicular phase): 0.66–14.7 mIU/mL; Prl: 3.85–30 ng/mL (81–623 mIU/L); and TT: 0.98–8.2 ng/dL (0.03–0.28 nmol/L). Conclusion We have established reference values of nine hormones used for the diagnosis and monitoring of PCOS in Pakistani and other populations of sub-continent.